A Survey of Benefit Approaches and Innovation Loop Required for IT Governance - Ghildyal, Amit; Chang, Elizabeth; Joiner, Keith (Archives of Business Research, 2018)
There has been a surge in adoption of the Benefit Management Approaches for Enterprise IT governance in recent years, particularly from many thought leaders including the White House, US Military, Australian Government and the like. This has led to the emergence of a new field of study Academically; Benefit Management for IT Governance. Our study shows that there is a need for an academic formalisation and a systematic approach of benefit management for IT projects and programmes. This can be used across wider enterprise governance of IT, particularly for the public sector, where benefits such as revenue and cost can be compelling. We, therefore, propose an innovation led Benefit Realisation Framework, a method for identifying the benefits and ensuring the benefit realisation. We offer proof of concept through case studies.